Effect of stimulus localisation on motion-onset VEP - Kremláček, J.; Kuba, M.; Chlubnová, J.; Kubová, Z. (Vision research (Oxford), 2004)
Reliable motion-onset visual evoked potentials (result of the dorsal stream activation) were recorded to motion stimuli with the temporal frequency of five cycles per seconds in 20 different locations with eccentricity up to 42° to periphery of the visual field. Amplitudes and latencies of the positive–negative–positive (P1–N1–P2; 84–144–208 ms) complex were evaluated in occipital (O Z and two derivations 5 cm to the left and right from O Z) and central region (C Z) in 10 subjects. We observed: (1) Shortening of the N1 latency toward periphery of the visual field. (2) The N1 amplitude maximum and latency minimum moved from occipital into central region (C Z derivation) as stimulus moved from centre toward periphery of visual field. (3) The P1 and N1 peaks displayed significantly greater amplitudes and shorter latencies when the lower part of the visual field was stimulated. (4) The N1 peak changed lateralisation of its maximum amplitude in dependence on the eccentricity. Up to 17°, it corresponds to striate projection of the “optic radiation” whilst more in periphery, there was paradoxical lateralisation of higher amplitude and shorter latency. The retinotopic dependence shows that the motion response includes position information and that the motion-onset VEPs are not generated solely in the higher extrastriate areas (MT or MST).